Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1182/blood.2019000095
|View full text |Cite
|
Sign up to set email alerts
|

LMO2 activation by deacetylation is indispensable for hematopoiesis and T-ALL leukemogenesis

Abstract: Key Points LMO2 is deacetylated by the NAMPT/SIRT2 pathway. LMO2 deacetylation is essential for LIM domain binding 1 binding and TAL1 complex activation during hematopoiesis and T-ALL leukemogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 93 publications
2
35
0
Order By: Relevance
“…We recently demonstrated that NAMPT and SIRT2 are essential for early blood cell formation 17 . The results of the present study complemented these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that NAMPT and SIRT2 are essential for early blood cell formation 17 . The results of the present study complemented these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of specific selective inhibitors of NAMPT and SIRT2 15,16 has made it possible to evaluate the specific roles of each of these factors in different physiological and pathological processes. We recently identified important roles of NAMPT and SIRT2 during early stages of hematopoietic differentiation of iPS cells using a feeder-free, serum-free monolayer-based differentiation protocol 17 . However, we did not study granulocytic differentiation of iPS cells using this method.…”
mentioning
confidence: 99%
“…It would be interesting to investigate whether NAMPT-triggered protein deacetylation governs the development of tissues and organs of mesoderm, endoderm or ectoderm origin, and whether SIRT2 or other SIRTs are involved. We recently demonstrated that NAMPT and SIRT2 are essential for early blood cell formation 17 . The results of the present study complemented these ndings.…”
Section: Discussionmentioning
confidence: 99%
“…A search for downstream targets of NAMPT/SIRT2 revealed that p53 is deacetylated by NAMPT/SIRT2 in iPS cells, leading to rapid and robust activation of p21 with subsequent cell cycle arrest and apoptosis of iPS cells. We recently reported that NAMPT deacetylates p53 in myeloid leukemia cells 17 . Our ndings in iPS cells further con rm the important role of NAMPT/SIRT2 in p53 deactivation through lysine deacetylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation